A Technology Based Program That Matches Enrichment Resources With Student Strengths - Renzulli, Joseph S.; Reis, Sally M. (International Journal of Emerging Technologies in Learning (iJET), 2007)
Remarkable advances in instructional communication technology (ICT) have now made is possible to provide high levels of enrichment and the kinds of curricular differentiation that facilitate advanced learning services to students who have access to a computer and the Internet. But in order to maximize the potential if ICT it is necessary to construct programs that are based on learning theory that goes beyond the didactic and prescriptive models that have resulted in too much worksheets-on-line and electronic encyclopedias. The Renzulli Learning System (RLS) uses a strength-based learning theory called the Enrichment Triad Model that is purposefully designed to promote advanced level learning, creative productivity, and high levels of student engagement by focusing on the application of knowledge rather than the mere acquisition and storage of information. The Renzulli Learning System is a comprehensive program that begins by providing a computer-generated profile of each studentâ??s academic strengths, interests, learning styles, and preferred modes of expression. A search engine then matches Internet resources to the studentâ??s profile from fourteen carefully screened data bases that are categorized by subject area, grade level, state curricular standards, and degree of complexity. There are also hundreds of enrichment activities that can be down loaded and reproduced for individual or group learning activities. A management system called the Wizard Project Maker guides students in the application of knowledge to teacher or student selected assignments, independent research studies, or creative projects that individuals or small groups would like to pursue. Students and teachers can evaluate the quality of studentsâ?? products using a rubric called The Student Product Assessment Form. Students can rate each site visited, conduct a self-assessment of what they have gained from the site, and place resources in their own Total talent Portfolio for future use. RLS also includes a curriculum acceleration management system for high-achieving students that is based on the many years of research and widespread use of a popular differentiation process called Curriculum Compacting.